Effects of pilates method on the posture, postural habits, and neck and back pain of women with temporomandibular dysfunction: A randomized clinical trial - Luiza Rampi Pivotto; Cláudia Tarragô Candotti; Juliana Adami Sedrez; Emanuelle Francine Detogni Schmit; Letícia Miranda Resende Da Costa; Jefferson Fagundes Loss (International Journal of Spine Research - Peertechz Publications, 2020)
Background: Associations between changes in body posture for people with Temporomandibular Dysfunction (TMD) have been discussed in the literature. Although the Pilates method is an alternative for treating postural changes, there is a lack of studies evaluating its effects on individuals with TMD. The purpose of the study is to investigate the effects of an exercise program based on the Pilates method on static posture, postural habits, and neck and low back pain in young women with TMD. 40 women between 18 and 35 years old with TMD were randomized into either a Control Group (CG), who received conventional treatment with myorelaxant plates, or an Intervention Group (IG), who received conventional treatment but were also submitted to an exercise program based on the Pilates method for 15 weeks, totaling 30 sessions. All subjects underwent the following: (1) assessment of neck and back pain and postural habits, (2) evaluation of posture by means of computerized photogrammetry, and (3) evaluation of TMD severity. The assessment was conducted prior to and following the intervention.  Results: There was a significant difference between the groups [F(1,37)=4.702; p=0.037; ŋ2=0.096], between the evaluative times [F(1,37)=8.951; p=0.005; ŋ2=0.023], and an interaction effect [F(1,37)=13.969; p=0.001; ŋ2p=0.274] for the TMD severity variable.  Conclusion: Regarding the exercise program based on the Pilates method, no effect was observed on neck and back pain, posture, and posture habits in young women with TMD. However, there was a decrease in the graduation of TMD severity after the intervention period only for the intervention group.